1046 Economic Burden of Short and Long Sleep Durations: An Analysis of the 2012 Medical Expenditure Panel Survey. (27th April 2018) - Jasani, F; Seixas, A; Madondo, K; Li, Y; Jean-Louis, G; Pagan, J
Abstract: Introduction: The current study investigated healthcare expenditures and utilization associated with short sleep ≤ 6 hrs., healthy sleep 7–8 hrs., and long sleep ≥ 9 hrs. durations across several health care service categories and chronic health conditions. Methods: Data on 6, 476 adults (age ≥ 18 years old) from the 2012 Medical Expenditure Panel Survey linked to the 2010–2011 National Health Interview Survey were analyzed. We used a two-part logit-generalized regression model to estimate total healthcare expenditures as well as expenditures for healthcare service categories such as emergency department visits, office-based visits, hospital-based outpatient visits, hospitalizations, home health care visits, and prescription drug. We estimated differences in annual expenditures for adults who reported short or long sleep duration, compared to individuals who reported healthy sleep (7–8 hrs.). Results: Total healthcare expenditures among short sleepers were 1, 400.33 higher than healthy sleepers; likewise among long sleepers they were 2, 994.29 based on unadjusted regression models (p<0.01). In the adjusted models, healthcare expenditures remained significantly higher (short sleepers; 988.53 and long sleepers; 867.10) relative to healthy sleepers (p<0.01). Compared to short and healthy sleepers, long sleepers had higher office-based, prescription, and home healthcare expenditures (p<.01). Of note, short sleepers had higher emergency department, hospital inpatient and outpatient expenditures compared to healthy and long sleepers (p<.01). We also investigated healthcare expenditures among short, healthy or long sleeper with a chronic condition. According to that analysis, long sleepers with hypertension had a higher healthcare expenditure (9, 665.49) compared to short or healthy sleepers. We also found that short sleepers with either a heart condition (10, 427.85), respiratory condition (6, 302.39), cancer (9, 061.01), or stroke (8, 118.44) had higher healthcare expenditures compared to their healthy and long sleepers. Surprisingly, we found those individuals with diabetes and who experienced 7–8 hrs. had a higher healthcare expenditure compared to short or long sleepers. Conclusion: This study underscores the potential impact of sleep on healthcare utilization costs and patterns, where short and long sleepers are characterized by higher long-term healthcare expenditures. Support (If Any): NIH/NHLBI K01HL135452, NIH/NIA K07AG052685.